The impact of service quality on customers satisfaction to Melaka Sentral Sdn Bhd (MSSB) / Muhammad Azman Ibrahim - Ibrahim, Muhammad Azman (Faculty of Business and Management, 2008)
The purpose of this research is to know the impact of service quality on customer satisfaction to Melaka Sentral Sdn Bhd (MSSB). Melaka Sentral Sdn Bhd (MSSB) not only provide the public transportation but other facilities such as fast food restaurant, ATM machine, toilet, prayers room, retail shop and so forth for making customers comfortable while they inside the terminal. Although the facilities are to make customers comfortable but there are complaints from customers about the service quality for example cleanness of the toilet, quality of the food that been sold by the restaurants, the service of the bus and so forth. The main objective of this research is to identify the level of customer satisfaction, level of service quality provided by Melaka Sentral Sdn Bhd (MSSB) and also to identify the most factors that influence the customer satisfaction. The research is conducted by using non probability sampling and the sampling method is convenience sampling. 50 of respondents have been asked by using questionnaire in order to gain information and feedback to the company. The questionnaire consists of question about the service quality dimensions and customers satisfaction towards Melaka Sentral Sdn Bhd (MSSB) service. The findings showed that most of the customers were agree and satisfy with the service that provided by Melaka Sentral Sdn Bhd (MSSB) at Terminal Melaka Sentral. Although the customers agree and satisfy with the service that Melaka Sentral Sdn Bhd provide, the company need to improve and maintain the service quality if they want build long-term relationship with their customers.